Type VI secretion in the plant growth promoting rhizobacteria Pseudomonas putida - Bernal,P; Civantos,C; Filloux,A; Llamas,MA (2015)
BackgroundBacterial type VI secretion systems (T6SSs) are recently discovered nanomachines used to inject effectors into prokaryotic or eukaryotic cells. Therefore, T6SSs are involved in both inter-bacterial competition and bacterial pathogenesis.ObjectivesThe aim is the study of the T6SS of Pseudomonas putida a soil bacterium with the capacity to colonise the root of crop plants. The colonisation by this bacterium provides growth advantages to the plant and, importantly, protection against plant pathogens. This makes P. putida a relevant biocontrol agent. Since T6SS is mainly used by environmental bacteria for interbacterial competition, one might speculate that T6SSs play a relevant role in the biocontrol properties of P. putida. Methods•in silico analysis of P. putida KT2440 genome •Competition assays to determine H1-T6SS activity and for the identification of H1-T6SS targets.•Regulatory studies: qRT-PCR, transcriptional fusionsConclusionsThe in silico analysis has revealed the existence of three putative T6SSs (H1, H2, and H3). The clusters contain the genes encoding the conserved core components and some accessories, including regulatory proteins and toxins-immunity pairs. Additional T6SS-related genes are found scattered on the chromosome.By competition assays we have determined that H1-T6SS is active and that mutants in H1-T6SS structural components lack the ability to kill model prey strains. Moreover, the system can be used to kill serious phytopathogens such as Pseudomonas syringae in in vitro assays. Interestingly, the H1-T6SS is induced in stationary phase and controlled by the global regulators RetS and GacS-GacA, and by two alternative sigma factors, RpoS and RpoN.